2020
DOI: 10.3389/fmicb.2020.01834
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Adaptation of Paracoccidioides brasiliensis in Response to in vitro Copper Deprivation

Abstract: Copper is an essential micronutrient for the performance of important biochemical processes such as respiration detoxification, and uptake of metals like iron. Studies have shown that copper deprivation is a strategy used by the host against pathogenic fungi such as Cryptoccocus neoformans and Candida albicans during growth and development of infections in the lungs and kidneys. Although there are some studies, little is known about the impact of copper deprivation in members of the Paracoccidioides genus. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Recent experiments in Paracoccidioides brasiliensis showed that copper deprivation has a major effect on fungal metabolism, but similar experiments have not been done in Coccidioides spp. [ 20 ]. In addition, a comparison of gene expression in C. posadasii spherules and an engineered chitinase deletion that does not endosporulate found that a major difference was the upregulation of iron and copper uptake genes, which is further evidence for the importance of iron and copper uptake for spherule and endospore formation [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent experiments in Paracoccidioides brasiliensis showed that copper deprivation has a major effect on fungal metabolism, but similar experiments have not been done in Coccidioides spp. [ 20 ]. In addition, a comparison of gene expression in C. posadasii spherules and an engineered chitinase deletion that does not endosporulate found that a major difference was the upregulation of iron and copper uptake genes, which is further evidence for the importance of iron and copper uptake for spherule and endospore formation [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this function, AOX also decreases the rate of mitochondrial ROS formation ( Maxwell et al, 1999 ; Vishwakarma et al, 2015 ). In fungi, low copper availability was shown to be connected to impaired respiration (cytochrome c oxidase pathway) ( Joseph-Horne et al, 2001 ), which generally leads to ROS accumulation in the mitochondria; thus, positive regulation of alternative oxidase may compensate for this loss and minimize ROS formation, which was recently demonstrated in Paracoccidioides brasiliensis ( Petito et al, 2020 ) and in C. albicans , where copper starvation led to mitochondrial SOD1 repression and AOX induction enhanced cytochrome c oxidase activity ( Broxton and Culotta, 2016 ). NDH-2 is a rotenone-insensitive nonproton pumping oxidoreductase that catalyzes a reaction similar to that of complex I, but in contrast to complex I, NDH-2 is not involved in the generation of membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genus Paracoccidioides change their protein expression, and consequently their metabolism and virulence, as a response to physiological conditions induced in experimental settings, such as copper overload [ 34 ], copper deprivation [ 35 ], acetate availability [ 31 ], osmotic stress [ 36 ], among others. The present work demonstrates that P. brasiliensis and P. lutzii , when grown in vitro in the presence of L-DOPA, a substance potentially available for the fungus during parasitism, not only produce melanin, as already described [ 13 , 14 ], but also undergo metabolic shifts and present differential abundance of proteins previously related with fungal virulence.…”
Section: Discussionmentioning
confidence: 99%
“…The glyoxylate cycle is associated with virulence in some human pathogenic fungi [ 48 , 49 ], and isocitrate lyase appears to have a role in adhesion and colonization of host tissues by P. brasiliensis [ 50 ], reinforcing the role of L-DOPA in the virulence enhancement of this species. The enzymes enoyl-CoA hydratase (PADG_01209) and acyl-CoA dehydrogenase (PADG_02244) were more abundant in melanized Pb 18, indicating β-oxidation of fatty acids in this strain, which also occurs when acetate is available for fungal growth [ 31 ], and during copper deprivation [ 35 ] or experimental infection [ 51 ]. It was noteworthy that the enzymes related to ethanol production did not present differential abundance between melanized and non-melanized cells of both strains tested.…”
Section: Discussionmentioning
confidence: 99%